PENGGUNAAN METODE DEMONSTRASI DENGAN CUTTING ENGINE UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISTEM PENGAPIAN SISWA KELAS XI SMK PERINDUSTRIAN YOGYAKARTA - Lucky Jati Padmanaba; Suparmin Suparmin (Jurnal Taman Vokasi, 2017)
The purpose of this study are: (1) determine the use of methods of demonstration with Cutting Engine can increase students' motivation on the subjects of the ignition system for class XI student of SMK Industry, Yogyakarta, and (2) to use methods of demonstration with Cutting Engine can improve student learning outcomes in subjects ignition system for class XI student of SMK Industry, Yogyakarta. This research is a classroom action research. Data collection techniques used in this study questionnaires and tests. This study design is divided into four stages, namely: (1) Planning (planning); (2) Implementation of the action (acting); (3) Observation (observing); and (4) Reflection (reflecting). Analysis of the data in this studyinclude: questionnaires, nalisis test data, and interviews. The results showed that pre-cyclestudent learning achievement results before there is action that has reached KKM 42.31 and57.69% who have not reached the KKM. After the action on the first cycle evaluation test and the value of the learning activities using the demonstration method Cutting Engine to improve motivation and student learning outcomes ignition system obtained by the students with an average of 68.57 which has not reached the KKM. In the second cycle students value greatly increased compared with the cycle of action I. After evaluation test scores and grades the second cycle of learning activities using the demonstration method Cutting Engine to improve motivation and learning outcomes of students is the ignition system with an averageof 73.19, p this has reached the KKM